“Innovación y estrategias cognitivas de aprendizaje, en el séptimo año de educación general básica, en la unidad educativa “Vicente León”, período 2022- 2023” - Analuiza Catota, Erik Fabian (2023)
Innovation through the use of cognitive strategies for learning integrating a critical framework development that involves relevant topics and sub-topics helped the research foundation of this study. The cognitive strategies development in seventh year’s students at E.G.B. It leads to achieving great challenges to all community of “Vicente León" Educational Unit, but mainly for teachers. Meanwhile, it implies significant changes in the teaching-learning process. The goal research was to investigate cognitive strategies through an investigative study according to the educational field that favors learning innovation. A quantitative-qualitative (mixed) methodological design has been applied, because it allowed interpreting, explaining, and exploring relevant aspects focused on digital didactic resources for teaching and learning in an innovative way to be treated in the classroom. The instrument was based on the questionnaire to seventh-year students Basic General Education and an interview guide to the teacher of the Educational Unit. The conclusions are connected to fixed perceptions at the beginning when referring to an innovation in learning on which the interest of strengthening the student body and its applicability is shown, favoring the cognitive development of the boys and girls of seventh E.G.B. Finally, a manual is proposed which will allow recording innovation through cognitive strategies to enhance the learning abilities’ students.